Syllable frequency and word frequency effects in spoken and written word production in a non-alphabetic script - Zhang, Qingfang; Wang, Cheng (Frontiers in Psychology, 2014)
The effects of word frequency and syllable frequency are well-established phenomena in domain such as spoken production in alphabetic languages. Chinese, as a non-alphabetic language, presents unique lexical and phonological properties in speech production. For example, the proximate unit of phonological encoding is syllable in Chinese but segments in Dutch, French or English. The present study investigated the effects of word frequency and syllable frequency, and their interaction in Chinese written and spoken production. Significant facilitatory word frequency and syllable frequency effects were observed in spoken as well as in written production. The syllable frequency effect in writing indicated that phonological properties (i.e., syllabic frequency) constrain orthographic output via a lexical route, at least, in Chinese written production. However, the syllable frequency effect over repetitions was divergent in both modalities: it was significant in the former two repetitions in spoken whereas it was significant in the second repetition only in written. Due to the fragility of the syllable frequency effect in writing, we suggest that the phonological influence in handwritten production is not mandatory and universal, and it is modulated by experimental manipulations. This provides evidence for the orthographic autonomy hypothesis, rather than the phonological mediation hypothesis. The absence of an interaction between word frequency and syllable frequency showed that the syllable frequency effect is independent of the word frequency effect in spoken and written output modalities. The implications of these results on written production models are discussed.